Effects of Task Difficulty and Perception of Distributive Justice on Social Loafing Among Senior Secondary School Students - Udoh , Emeh A; Otioro, Winifred G. (Journal of Advanced Psychology, 2021)
Purpose: This study investigated effects of task difficulty and perception of distributive justice on social loafing. Methodology: Twenty-eight (28) participants comprising 14 males (50%) and 14 Females (50%) randomly selected from a population of Senior Secondary 2 Students (SS2) in Foundation Comprehensive College Okoloma Afam, Oyibo Local Government Area, Rivers State participated in the study. Participants were drawn using purposive sampling technique and the simple random sampling techniques. The ages of participants ranged between 14 - 15 years and their mean age was 14.75 years. The study was experimental. The perception of distributive justice scale and social loafing scale were the instruments used in the study. The design of the study was a 2x2 Factorial Design. A 2-way Analysis of Variance was employed for data analysis. Findings: The results of the study revealed that task difficulty has a significant effect of on social loafing (F (1, 27) = 5.48; P<0.5). The results also revealed that perception of distributive justice has a significant effect on social loafing (F (1, 27) =11.14; P<0.5). In addition, results revealed no significant interaction effect between task difficulty and perception of distributive justice on social loafing. Unique contribution to theory, practice and policy: Implications and recommendations were made on the basis of the findings of the study.